T cells are the critical source of IL-4/IL-13 in a mouse model of allergic asthma - Oeser, Katharina; Maxeiner, J.; Symowski, Cornelia; Stassen, M.; Vöhringer, David (Allergy, 2015)
IL-4 and IL-13 play a crucial role during allergic asthma. Both cytokines can be produced by T cells and a variety of cell types of the innate immune system. The relative contribution of T-cell-derived vs innate IL-4/IL-13 for allergic inflammation and airway hyperreactivity remains unclear.We compared the severity of OVA/alum-induced allergic lung inflammation in WT BALB/c mice to mice that lack expression of IL-4/IL-13 only in T cells (4-13Tko) or in all cell types (4-13ko).T-cell-derived IL-4/IL-13 was required for IgG1 and IgE production, recruitment of eosinophils and basophils to the lung, goblet cell hyperplasia, expression of Muc5ac, Clca3, and RELM?, differentiation of alternatively activated macrophages, and airway hyperreactivity. Interestingly, ILC2 recruitment to the lung occurred independently of T-cell-derived IL-4/IL-13 but was diminished in the absence of IL-4/IL-13 from all cell types. Thus, the number of IL-4/IL-13-competent ILC2s did not correlate with the severity of lung pathology.Th2 cells appear to be the critical IL-4/IL-13-expressing cell type for the induction of allergic airway inflammation and airway hyperreactivity. The translational perspective of our results indicates that inhibition or reprogramming of Th2 cells may be very effective for the treatment of allergic asthma.
EVALuna2:25864